2021
DOI: 10.1002/er.6899
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of MXenes as catalyst supports for the oxygen reduction reaction in fuel cells

Abstract: The oxygen reduction reaction (ORR) that occurs in the cathode of fuel cells is a major issue in proton exchange membrane fuel cells (PEMFCs) due to their sluggish kinetics. Exploring suitable materials for use as cathode catalysts can be challenging because the materials should be chemically active yet must be stable in an extremely corrosive environment in fuel cells. Since the successful introduction of graphene, 2-dimensional (2D) materials have received extensive research interest regarding their use as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 215 publications
(211 reference statements)
1
31
0
Order By: Relevance
“…To further investigate the effect of substitution on the metal site of TMPS 3 (100) surface, we have substituted half of the Mn atomic sites (50 %) with Fe, Co and Ni of MnPS 3 (100) surface, the best surface for ORR. As reported earlier, substitution on metal sites of TMDs, [38] TMPs, [39] Mxenes, [40] as well as various alloys namely Pt 3 Co [41] and Pt 3 Cr [41] improves ORR activity. Moreover, the presence of adjacent dual unlike metal sites in a catalyst is reported to enhance ORR efficiency [42] …”
Section: Resultssupporting
confidence: 57%
“…To further investigate the effect of substitution on the metal site of TMPS 3 (100) surface, we have substituted half of the Mn atomic sites (50 %) with Fe, Co and Ni of MnPS 3 (100) surface, the best surface for ORR. As reported earlier, substitution on metal sites of TMDs, [38] TMPs, [39] Mxenes, [40] as well as various alloys namely Pt 3 Co [41] and Pt 3 Cr [41] improves ORR activity. Moreover, the presence of adjacent dual unlike metal sites in a catalyst is reported to enhance ORR efficiency [42] …”
Section: Resultssupporting
confidence: 57%
“… 11 Among these materials, MXenes (M n +1 X n ), synthesized by eliminating the A-layer from their bulk counterpart the MAX phase (M n +1 AX n , M refers to early transition metals, “A” represents the group of sp elements, “X” represents C or N atoms, and n is 1, 2, 3), has received wide research attention 12 due to a wide range of applications in Li-ion batteries, 13 catalysis, 14 electrochemical capacitors 15 and also in fuel cells. 16 The M–X bond in the MAX crystals is stronger than the M–A bond, making it possible to etch “A” atoms between the M n +1 X n layer. 17 All the MXenes are metals, while appropriate surface termination (M n +1 X n T x , T x denotes surface terminations, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…MXenes as ORR catalysts when coupled with platinum group metals show excellent ORR activity and it shows performance higher than that of the benchmarking catalyst Pt/C, and some of the transition metal atoms coupled MXenes also show good performance indicating a good synergy. 142 Fei et al, reported polyimidazole/MXene composite the oxygen terminations of MXene enhanced the performance of the intermediate temperature PEMFC which delivered a power density of 209 mW cm À2 at 150 C. 143 Xu et al developed MXene with Pt and CNT support the mass activity of the materials was around 3.4-fold more compared to Pt/C and the PEMFC showed a high-power density of 138 W of the fuel cell stack. 144 Tahir et al modified carbon-felt electrode by NiFe 2 O 4 -MXene@CF using conventional dip and dry followed by a hydrothermal method, the performance of the microbial fuel cell was increased and it showed a high energy density of 1385 mW m À2.…”
Section: Mxenes As Electrocatalyst In Fuel Cell Applicationsmentioning
confidence: 99%
“…MXene as electrocatalyst for ORR is considered to be best catalyst due to their electronic properties, chemical and physical properties (high surface area) and good electrical conductivity. MXenes as ORR catalysts when coupled with platinum group metals show excellent ORR activity and it shows performance higher than that of the benchmarking catalyst Pt/C, and some of the transition metal atoms coupled MXenes also show good performance indicating a good synergy 142 . Fei et al, reported polyimidazole/MXene composite the oxygen terminations of MXene enhanced the performance of the intermediate temperature PEMFC which delivered a power density of 209 mW cm −2 at 150°C 143 .…”
Section: Mxene As Electrocatalyst For Her Oer and Orr In Water Splitt...mentioning
confidence: 99%